DIFFUSE CONTINENTAL DEFORMATION - LENGTH SCALES, RATES AND METAMORPHIC EVOLUTION - England, P (1987)
In contrast with the oceanic portions of the plates, continents may deform 100's of km away from any plate boundary. Calculations that treat the continents as continuous media suggest that the across-strike length scale of deformation associated with a convergent boundary is proportional to the along-strike length of the boundary, the constant of proportionality depending on the rheology of the lithosphere. Metamorphism in crust that is subject to major extension following compressional orogenesis should be nearly independent of the initial thermal conditions of the crust, and may be distinguished from metamorphism terminated by erosion by a final stage of isobaric cooling from temperatures close to the maximum experienced. -from Author